Midwifery Care for Postpartum Mothers 2 Days Ny C P1A0 Perineal Wounds with Gabus Fish Floss to Aid Healing at TPMB BD. Nilawarni, Asahan Regency - Dwi Feni Pebriani Br Tarigan; Dina Aulia Putri (Sean Institute, 2025)
The postpartum period is an important time for mothers after childbirth, requiring optimal midwifery care, especially for mothers with perineal wounds. Perineal wounds can cause pain, discomfort, and risk infection if not treated properly. One non-pharmacological measure that can help speed up the healing process of perineal wounds is adequate nutrition, especially protein and albumin. Snakehead fish (Channa striata) is known to have high albumin and protein content, which has the potential to accelerate tissue regeneration. This case study aims to provide midwifery care to a postpartum mother on her second day, Mrs. C P:1 A:0, with a perineal wound through the provision of snakehead fish floss at the TPMB Bd. Nila Warni S.Keb, Asahan Regency, in 2025. The method used was a case study with a midwifery care management approach that included assessment, diagnosis, planning, implementation, and evaluation. The results of the care showed a gradual improvement in the condition of the perineal wound, a reduction in pain, and optimal healing after consuming snakehead fish floss for seven consecutive days. The conclusion of this case study is that the administration of catfish abon can be an effective nutritional intervention alternative in helping to accelerate the healing of perineal wounds in postpartum mothers.